Molecular evidence for human population change associated with climate events in the Maya lowlands. (15th April 2021) - Keenan, Benjamin; Imfeld, Anic; Johnston, Kevin; Breckenridge, Andy; Gélinas, Yves; Douglas, Peter M.J.
Abstract: The analysis of faecal stanols in lake sediment cores offers a novel opportunity to reconstruct human population change, assuming that variability in faecal stanol concentration is a reliable proxy for relative human populations. The ancient lowland Maya of Mesoamerica represents an important ancient society whose demographic dynamics in many locations remain uncertain. We apply the faecal stanol proxy to a sediment core retrieved from a lake adjacent to the archaeological site of Itzan, an ancient population centre in the southwestern Maya lowlands. The sedimentary faecal stanol record from Laguna Itzan implies substantial centennial- and millennial-scale changes in local human populations from 3300 cal years BP to the present. Variability in faecal stanol concentrations is broadly consistent with archaeological evidence for regional societal change across the Maya lowlands, but also implies an earlier presence of humans at this site than is currently indicated in the Itzan archaeological record. We find evidence for high-frequency variability in coprostanol concentrations during the Maya Preclassic period, which we infer represents centennial-scale shifts in settlement patterns associated with changes in agricultural and land use patterns. Given Preclassic-period faecal peak stanol concentrations, we observe lower-than-expected Classic-period faecal peak stanol concentrations, and these may partly be a result of either use of human waste for fertiliser or reduced soil erosion or both. Three periods of inferred population decline are associated with palaeoclimate evidence for a drying climate, specifically during the Terminal Classic (1220-1050 cal yr BP) and the Protoclassic 2 (1860-1670 cal yr BP), as well as the less well-studied drought between 3330 and 2900 cal yr BP during the Early to Middle Preclassic periods. An additional decline and hiatus in coprostanol input coincides with a period of anomalously wet climate in the Late Preclassic. These linkages suggest that climatic change and variability could have played a role in demographic change at multiple points in the evolution of Maya civilisation. Our work shows that faecal stanols are valuable proxies for past human population dynamics, and their relation to climatic change, in Mesoamerica. Highlights: Faecal stanols used to reconstruct population change in Maya lowlands. Stanol variation consistent with archaeological evidence for societal change. Presence of humans at site much earlier than indicated in archaeological record. Population decline associated with drying climate as well as a wet period. Possible use of human waste as fertiliser ("night soil").